The historical framework of the orientalists stands from the Quranic readings: An analytical study / Mohd Shamsul Hakim Abd Samad - Mohd Shamsul Hakim, Abd Samad (2016)
The involvement of the Orientalists in the studies on Islam and its various branches of knowledge is certainly inevitable. Since the 18th century, the findings related to Islam covering all fields of Islamic study have been published by the orientalists. These reviews regard the study of the Eastern world concerning all aspect of life, including social, political, economic, cultural and belief systems. The followed method of this study are inductive dan deductive method. Thus, this study will circle around historical framework of orientalist opinion against Qirā’āt al-Quran and the analysis of such opinion in relation to the historical study and their stand. This study starts with the definition of the orient and orientalist and relevant terminologies used by them from ancient times until the present day. Then, this study will discuss on the history of the orientalist and the objectives of its establishment in order to understand the nature of their activities which are against Muslims in general and al-Quran specifically. This study will also discuss the historical context of orientalist participation in the study of al-Quran and Qirā’āt al-Quran, the undelying reason and their involvement in that study. The study will be continued by presenting the brief opinion of the orientalist on both al-Quran and Qirā’āt al-Quran by relying to the written evidence for instance their essays and publication. Through participation in the study of the research history on Qirā’āt al-Quran, this study will be able to pictures the implication of the orientalist involvement in this field either positive or negative angle. The findings of this study shows that there five of positive impacts, and three of negative impacts. Furthermore, the results of this study will be gathered at the end of the review clause accompanied with suggestions and recommendation for this religion and its followers beloved.